Effects of thymosin β4 and its N-terminal fragment Ac-SDKP on TGF-β-treated human lung fibroblasts and in the mouse model of bleomycin-induced lung fibrosis. (July 2015) - Conte, Enrico; Iemmolo, Maria; Fruciano, Mary; Fagone, Evelina; Gili, Elisa; Genovese, Tiziana; Esposito, Emanuela; Cuzzocrea, Salvatore; Vancheri, Carlo
<x xml:space="preserve">Abstract</x> Thymosin β4 (Tβ4) and its amino-terminal fragment comprising N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) have been reported to act as anti-inflammatory and anti-fibrotic agents in vitro and in vivo. In recent papers, we have shown that Tβ4 exerts a widely protective role in mice treated with bleomycin, and in particular, we have demonstrated its inhibitory effects on both inflammation and early fibrosis. Objectives: In this study, the putative anti-proliferative and anti-fibrogenic effects of Tβ4 and Ac-SDKP were evaluated in vitro. In addition, the effects of Tβ4 up to 21 days were evaluated in the bleomycin mouse model of lung fibrosis. Methods: We utilized both control and TGF-β-stimulated primary human lung fibroblasts isolated from both idiopathic pulmonary fibrosis (IPF) and control tissues. The in vivo effects of Tβ4 were assessed in CD1 mice treated with bleomycin. Results: In the in vitro experiments, we observed significant anti-proliferative effects of Ac-SDKP in IPF fibroblasts. In those cells, Ac-SDKP significantly inhibited TGF-β-induced α-SMA and collagen expression, hallmarks of fibroblast differentiation into myofibroblasts triggered by TGF-β. In vivo, despite its previously described protective role in mice treated with bleomycin at 7 days, Tβ4 failed to prevent fibrosis induced by the drug at 14 and 21 days. Conclusion: We conclude that, compared to Tβ4, Ac-SDKP may have greater potential as an anti-fibrotic agent in the lung. Further in vivo experiments are warranted.